Seven years follow-up of corneal cross-linking (CXL) in pediatric patients: Evaluation of treated and untreated eye. Issue 3 (May 2022) - Simantov, Iliya; Or, Lior; Gazit, Inbal; Dubinsky-Pertzov, Biana; Zadok, David; Pras, Eran; Hartstein, Morris; Einan Lifshitz, Adi
Background: Retrospective cohort study evaluating long term keratoconus progression amongst cross-linking (CXL) treated pediatric patients in the treated and the fellow untreated eyes. Methods: Data on 60 eyes of 30 patients, 18 years old or younger, who underwent CXL in at least one eye was collected and analyzed. Follow-up measurements taken from the treated and untreated eye up to 7 years after CXL treatment, were compared to baseline measurements. Parameters included uncorrected distance visual acuity (UCDVA), best-corrected spectacle visual acuity (BCSVA), manifest refraction, pachymetry, corneal tomography, and topography. Results: Mean age of patients was 16 ± 2.1 years. For the treated eyes, during follow-up period mean UCDVA had improved (from 0.78 ± 0.22 at baseline to 0.58 ± 0.26 logMAR at 7 years; p  = 0.13), as well as mean BCSVA (from 0.23 ± 0.107 at baseline to 0.172 ± 0.05 logMAR at 7 years; p  = 0.37). The mean average keratometry showed a significant flattening (from 49.95 ± 4.04 to 47.94 ± 3.3 diopters (D); p  < 0.001), However there was no change in the mean maximal keratometry. The mean minimal corneal thickness (MCT) showed a significant mild reduction of 26 µm ( p  = 0.006). Although statistically insignificant, the mean manifest cylinder was also reduced to 2D ( p  = 0.15). During the follow-up period, eight untreated eyes (26.6%) deteriorated and underwent CXL, while only one treated eye (3.33%) required an additional CXL. Conclusion: CXL is a safe and efficient procedure in halting keratoconus progression in the pediatric population, the fellow eye needs to be carefully monitored but only a 25% of the patients will require CXL in that eye during a period of 7 years.